Blending of TiO2 nanoparticles with cellulose acetate polymer: to study the effect on morphology and gas permeation of blended membranes. Issue 4 (29th January 2014) - Farrukh, Sarah; Javed, Sofia; Hussain, Arshad; Mujahid, Muhammad
ABSTRACT Cellulose acetate–titania (CA–TiO2) nanoparticles blended membranes were fabricated using diffusion‐induced phase separation process to observe the effect of inorganic nanofillers on the surface topography and gas permeation properties of CA membrane. Self‐synthesized TiO2 nanoparticles using sol gel reflux condensation were employed as nanofillers, which is the anatase phase of TiO2 with crystallite size of 5–10 nm. The synthesized membranes were characterized using scanning electron microscopy and atomic force microscopy techniques to study the nanoscale distribution of TiO2 nanoparticles, surface roughness, and pores generation in blended membranes, with increasing nanoparticles' concentration in polymer matrix. The permeability of CO2 was found to be increased for CA–TiO2 blended membranes. The CO2/CH4 selectivity up to 23.3 was documented. © 2014 Curtin University of Technology and John Wiley & Sons, Ltd.